The New Organic Molecule-Based Epoxy Resin as an Effective Corrosion Inhibitor for Mild Steel in Sulfuric Acid Medium - Benabida, A.; Aouni, N. EL; Galai, M.; El Assyry, A.; Dagdag, O.; Cherkaoui, M.; El Harfi, A.; Zarrouk, A. (Protection of metals and physical chemistry of surfaces, 2021)
The influence of organic molecule based from Epoxy Resin Octa-functional (REO) on the corrosion inhibition of mild steel in the presence of 0.5 M H 2 SO 4 at different temperatures have been studied using polarization, EIS and computational methods. Polarization curves indicate that REO is a mixed inhibitor. EIS measurements show an increase of the transfer resistance with increasing inhibitor concentration. The inhibition efficiency of REO reaching 98% was observed at 10 –3 M concentration. The inhibitor adsorption is chemical adsorption compound using the Langmuir adsorption isotherm. The free adsorption energy and the influence of temperature on the inhibitor adsorption onto mild steel surface have been reported. Calculated values confirm that the adsorption mechanism of this inhibitor on mild steel in 0.5 M H 2 SO 4 solution is a chemical adsorption. The quantum chemical calculations were applied to elucidate adsorption pattern of inhibitor molecules on the steel surface.